A comparative UPLC-Q-TOF/MS-based metabolomics approach for distinguishing peach (Prunus persica (L.) Batsch) fruit cultivars with varying antioxidant activity. (November 2020) - Zhang, Xianan; Li, Xin; Su, Mingshen; Du, Jihong; Zhou, Huijuan; Li, Xiongwei; Ye, Zhengwen
Graphical abstract: Highlights: Both metabolites profile and antioxidant activities were varied among tested 40 peach cultivars. PLS regression model confirmed key compounds in peach pulp contributing to antioxidant activity. Procyanidins and phloridzin were screened out as antioxidant marker compounds of peaches. Abstract: Peaches ( Prunus persica (L.) Batsch) are nutritionally and economically important and they are one of the most popular fruits consumed worldwide. Understanding metabolite-caused bioactivity differences among cultivars is essential for designing a peach with enhanced nutritional traits. In this study, we report an untargeted UPLC-Q-TOF/MS-based metabolomics approach for comprehensively discriminating between peaches with different antioxidant activities. Mature fruit from 40 peach cultivars were distinguished using principal component analysis and orthogonal partial least squares discrimination analysis. Seventeen differential metabolites were tentatively identified between peach cultivars with high and low antioxidant potency composite indices, and eight metabolites, including procyanidin C1, procyanidin trimer isomer 1, procyanidin trimer isomer 2, procyanidin B1, procyanidin B2, procyanidin B3, prunus inhibitor b, and phloridzin, were identified as marker compounds responsible for the discrimination of the cultivars base on potential antioxidant activity. Our study highlights the essence and predictive power of metabolomics for detecting small differences and for identifying potential marker metabolites based on their levels and composition in plants exhibiting varying bioactivities. Overall, the variations in the metabolites in peach pulp reflected the diversity in the peach germplasm, and these eight compounds are good candidate markers for future genetic breeding of peach fruit with enhanced antioxidant activity.